Legal Regulations and the Perspectives of Renewable Energy Policy in Selected EU Member States - Eleonóra Marišová; Ján Gaduš; Martin Mariš; Agnieszka Parlińska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The main objective of the paper is an evaluation of the development of the use of the RES in V4 countries compared to the EU-28 average and assessment, if national strategic goals regarding the share of the RES on gross inland energy consumption are achievable till 2020. To achieve the main aim of the paper it was decided to apply Brown triple exponential smoothing model as a main research method. Based on gathered results and using the extrapolation for making the forecast till do 2020 it was found out, that Slovakia might track the national target with point estimation of 16.25% (90% CI: 13.98:18.53), Czech Republic 12.75% (90% CI: 10.44:15.06), Poland 19.9% (90% CI: 16.42: 23.37). In case of Hungary, it might fail to reach the national target with point estimation of 10.42% (90% CI:8.87:11.98) and overall EU in average will not be able to reach common target with point estimation of 15.94% (90% CI:13.08:18.8).